On compressed zero divisor graphs associated to the ring of integers modulo n - Aijaz, M.; Rani, K.; Pirzada, S. (Carpathian Mathematical Publications, 2023)
Let R be a commutative ring with unity 1 e 0. In this paper, we completely describe the vertex and the edge chromatic number of the compressed zero divisor graph of the ring of integers modulo n. We find the clique number of the compressed zero divisor graph Γ_E(Z_n) of Z_n and show that Γ_E(Z_n) is weakly perfect. We also show that the edge chromatic number of Γ_E(Z_n) is equal to the largest degree proving that Γ_E(Z_n) resides in class 1 family of graphs.